Determination the site of antibiotic resistance genes in Escherichia coli isolated From Urinary Tract Infection - Mohammad, Karzan Abdulmuhsin; Ahmed, Zirak F.; Mohammed, Bayar A; Saeed, Rasti H (Kurdistan Journal of Applied Research, 2018)
This study includes isolation of 25 isolates of Escherichia coli (E. coli ) strain from urinary tract samples in a pregnant woman. Microbiological and biochemical tests were used to identify the resistant bacteria of this genus. Screening methods were used to determine bacterial isolates for their resistance to 10 antibiotics include: Amikacin (Ak), Amoxicillin (Ax), Ampicillin (Ap), Chloramphenicol (Cm), Ciprofloxacin (Cip), Erythromycin (Er), Nalidixic acid (Nal), Penicillin (Pen), Tetracycline (Tet) and Trimethoprim (Tm). The isolates E4, E9, E16, and E17 were resistant to all antibiotics used in the current study using the disk diffusion method. In contrast, the resistance percentage for all antibiotics ranged between 28-96%. Sites of resistance genes and hemolysin production genes were characterized by tranformation techniques in the E4 and E16. The results showed that the antibiotic resistance genes of Amikacin, Erythromycin, Tetracyclin, and Trimethoprim were located on a plasmid, whereas Amoxicillin, Ampicillin, Chloramphenicol, Ciprofloxacin, Nalidixic acid and Penicillin were located on chromosomal DNA. The results also demonstrated an inability to produce alpha or beta-hemolysin indicating that the genes which are responsible for hemolysin production were also located on chromosomal DNA.